Ci??ncia na rede: populariza????o da ci??ncia no canal Nerdologia - Sousa, Renata de Lima (2020)
Submitted by Renata Sousa (renatalima.dl@gmail.com) on 2020-01-20T00:56:09Z No. of bitstreams: 4 Disserta????o_RenatadeLima_Final.pdf: 2064162 bytes, checksum: c3899cfdcd8b77be98c52c1eda1ba651 (MD5) CartaEncaminhamentoAutodep??sito_Renata.pdf: 143206 bytes, checksum: cb628307a461dca1f2da8b9f4588e8ed (MD5) Ata de defesa_Renata.pdf: 574325 bytes, checksum: aa12026093a6375524c4d2e9303e7076 (MD5) license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5)